A sketch grammar of Seletar - Tan, Zhi Xuan (Nanyang Technological University, 2023)
The thesis presents a sketch grammar of Seletar, the language of the Orang Seletar. The Orang Seletar are one of the many Orang Asli (‘indigenous people’) of Malaysia and one of Singapore’s indigenous sea peoples (Orang Laut). The language is spoken by approximately 2,000 people in Johor Bahru, Malaysia. The research done on the Orang Seletar often lacks technical linguistic analysis based on natural speech, so the thesis hopes to fill this gap. The thesis covers phonology and morphosyntax up to the level of complex sentences.